3-Nitro-1H-1,2,4-triazole - Hoong-Kun Fun; Madhukar Hemamalini (Acta Crystallographica Section E, 2011)
The asymmetric unit of the title compound, C2H2N4O2, contains two crystallographically independent molecules in which the triazole rings are essentially planar, with maximum deviations of 0.003 (1) Å in both molecules. The dihedral angle between the two 1H-1,2,4-triazole rings is 56.58 (5)°. In the crystal, molecules are linked via intermolecular N—H...N and C—H...O hydrogen bonds, forming a supramolecular chain along the b axis.